Hinglaj Devi: Identity, Change, and Solidification at a Hindu Temple in Pakistan, by Jurgen Schaflechner - Joffrey, Fizza (Religions of South Asia, 2021)
Hinglaj Devi: Identity, Change, and Solidification at a Hindu Temple in Pakistan, by Jurgen Schaflechner. Oxford: Oxford University Press, 2018. xiii + 343 pp., £85.96 (hb). ISBN 978-0-19-085052-4 (hb).